Pipe Network Evaluation for "X" Field Production Optimization - Slamet Widodo Kurniansyah; Esaim Mustafa Abrahim Omar; Dwi Atty Mardiana (Journal of Earth Energy Science, Engineering, and Technology, 2020)
Fields "X" is an old field in the South East Sumatra Block. The area was developed using ten platforms. One main problems on this field is the disruption of some wells productivity due to flow constraints in the piping network. The objective of this paper is to evaluate the pipeline network for area "X1" using simulation model. The simulation results show that there are bottlenecking and backpressure problems in the network. By fixing the problems, total oil production in this area can be increased up to 19 percent or 1,006.2 BOPD higer than initial condition.